Knowledge Management Experience in Malaysian Schools - Yusof, Hamidah; Yusof, Rohaila; Norwani, Norlia Mat; Mansor, Mahaliza (International Business Education Journal, 2015)
Nowadays, knowledge management has become an important element in the success of an organization including schools. In relation to that, this study was conducted to investigate the elements of knowledge management in Malaysian schools. Knowledge management in this study was measured by the elements vision and mission, strategy, organizational culture, intellectual capital, learning organization, leadership and management, teamwork and learning communities, sharing knowledge, knowledge creation and digital sophistication proposed by Sallis and Jones. This study was investigated the relationship between principals’ experience and age with the elements of knowledge management in the Malaysian schools based on teachers’ perceptions. A number of 132 teachers were selected as respondents from 3 schools which included primary and secondary schools. This study used a set of questionnaire to gain the teachers’ views on knowledge management. Data was analyzed descriptively. Overall, schools in Malaysia had shown high mean score for every element of knowledge management in this study and it can still be improved. All the elements have significant, weak relationships with the principals’ experiences, The elements of vision, mission and organization strategy showed significant relationships with principals’ age but the relationship was also weak.